Electroextraction and electromembrane extraction: Advances in hyphenation to analytical techniques. Issue 9 (31st March 2016) - Oedit, Amar; Ramautar, Rawi; Hankemeier, Thomas; Lindenburg, Petrus W.
Abstract : Electroextraction (EE) and electromembrane extraction (EME) are sample preparation techniques that both require an electric field that is applied over a liquid‐liquid system, which enables the migration of charged analytes. Furthermore, both techniques are often used to pre‐concentrate analytes prior to analysis. In this review an overview is provided of the body of literature spanning April 2012–November 2015 concerning EE and EME, focused on hyphenation to analytical techniques. First, the theoretical aspects of concentration enhancement in EE and EME are discussed to explain extraction recovery and enrichment factor. Next, overviews are provided of the techniques based on their hyphenation to LC, GC, CE, and direct detection. These overviews cover the compounds and matrices, experimental aspects (i.e. donor volume, acceptor volume, extraction time, extraction voltage, and separation time) and the analytical aspects (i.e. limit of detection, enrichment factor, and extraction recovery). Techniques that were either hyphenated online to analytical techniques or show high potential with respect to online hyphenation are highlighted. Finally, the potential future directions of EE and EME are discussed.